The Federal Democratic Republic of Ethiopia : Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report ;, 2009)
Ethiopia's request for disbursement under the rapid-access component of the Exogenous Shocks Facility is examined. The authorities have embarked upon a tightening of monetary and fiscal policies to facilitate necessary rebuilding of foreign exchange reserves. Wheat has been imported on an emergency basis to dampen domestic inflation expectations and alleviate the impact of high food prices on vulnerable groups. Steep increases in international prices for key imports have exacerbated strains on the Ethiopian economy and pushed foreign exchange reserves to critically low levels.